STUDI PERUBAHAN PROTEIN TERLARUT SELAMA PERKECAMBAHAN BIJI KORO BENGUK (MUCUNA PRURIENS L.) - Suhendra, Lutfi (Agrotekno; Vol. 12, No. 1 Februari 2006, 2012)
The research objective was to study the soluble protein change during process seed germination. Seed sprout were made in dark room at the room temperature (30 0C) with several combination treatment of 3 factor in 5 levels for each factor. The factors are (i) duration of germination process; (ii) duration of soaking process; and (iii) pH of soaking solution. The analysis of soluble protein was undertaken from extracted sprouts. Data was analysed by using the Respon Surface Methodology (RSM) with the central composite design (CCD). The research results indicated that the maximum of soluble protein (the incubation of 24 hour in temperature 50 0C with minimum value 9.78% wet weight) was obtained from the process of 8 days of germination process, 36 hours of soaking process and in pH of 6.
Keywords: Protein terlarut, kecambah biji, Mucuna pruriens L., response surface methodology